Effect of continuous planting on Casuarina equisetifolia rhizosphere soil physicochemical indexes, microbial functional diversity and metabolites - Wang, Yuhua; Li, Jianjuan; Li, Mingzhe; Jia, Xiaoli; Cai, Yuhong; Hu, Mingyue; Zhang, Qingxu; Cheng, Pengyuan; Lin, Shaoxiong; Lin, Wenxiong; Wang, Haibin; Wu, Zeyan (Frontiers in Plant Science, 2023)
Continuous planting has a severe impact on the growth of Casuarina equisetifolia. In this study, the effects of three different long-term monocultures (one, two and three replanting) on the physicochemical indexes, microbial functional diversity, and soil metabolomics were analysed in C. equisetifolia rhizosphere soil. The results showed that rhizosphere soil organic matter content, cation exchange capacity, total and available nitrogen, total and available phosphorus, and total and available potassium contents significantly decreased with the increasing number of continuous plantings. The evaluation of microbial functional diversity revealed a reduction in the number of soil microorganisms that rely on carbohydrates for carbon sources and an increase in soil microorganisms that used phenolic acid, carboxylic acid, fatty acid, and amines as carbon sources. Soil metabolomics analysis showed a significant decrease in soil carbohydrate content and a significant accumulation of autotoxic acid, amine, and lipid in the C. equisetifolia rhizosphere soil. Consequently, the growth of C. equisetifolia could hinder total nutrient content and their availability. Thus, valuable insights for managing the cultivation of C. equisetifolia and soil remediation were provided.